EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN DISCOVERY LEARNING (DL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA - Wicaksana, Hafid; Mardiyana, Mardiyana; Usodo, Budi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: This research aimed to know: (1) which one of thelearning models give a better achievement between PBL, DL, or classical with scientific approach, (2) which one has a better achievement between the student categorization, climbers, campers, or quitters, (3) at adversity quotient categorization, which one of the learning models give a better achievement between PBL, DL, or classical with scientific approach, and 4) at each the learning models, which one of the adversity quotient have a better achievement between student categorization, climbers, campers, or quitters. This was a quasi-experimental study. The research population were the seventh-grade students of all state junior high schools in Sukoharjo Regency in the academic year of 2014/2015. The data were analyzed through hypothesis testing using two-way ANOVA with unequal cells.Based on the analysis, the following conclusions are drawn. 1) The PBL model generates better learning outcomes than the DL model and the classical learning model using scientific approaches. The DL model generates better learning outcomes than the classical learning model using scientific approaches. 2) The students in the climber category have better learning outcomes than those in the camper category and the ones in the quitter category. The students in the camper category have better learning outcomes than those in the quitter category. 3) In the climber category, the students taught using the scientific PBL model have better learning outcomes in mathematics than those taught either using the scientific DL model or the classical learning model with scientific approaches. In the camper category, the students taught using the scientific PBL model have equal learning outcomes in mathematics to those taught using the scientific DL model but they have better learning outcomes than the students of the same category taught using the classical learning model with scientific approaches. 4) In relation to the PBL model using scientific approaches, the learning outcomes of the students in the climber category are better than those in the categories of campers and quitters. The students in the camper category have equal learning outcomes to those in the quitter category. In relation to the DL model using scientific approaches, the learning outcomes of the students in the climber category are equal to those in the camper category and better than those in the quitter categories.Keywords: Problem-Based Learning, Discovery Learning, Classical, Scientific Approaches, Adversity Quotient, Achievement.